The TikTok Addiction Scale: Development and validation - Petros Galanis; Aglaia Katsiroumpa; Ioannis Moisoglou; Olympia Konstantakopoulou (AIMS Public Health)
BackgroundThere is an absence of valid and specific psychometric tools to assess TikTok addiction. Considering that the use of TikTok is increasing rapidly and the fact that TikTok addiction may be a different form of social media addiction, there is an urge for a valid tool to measure TikTok addiction.ObjectiveTo develop and validate a tool to measure TikTok addiction.MethodsFirst, we performed an extensive literature review to create a pool of items to measure TikTok addiction. Then, we employed a panel of experts from different backgrounds to examine the content validity of the initial set of items. We examined face validity by performing cognitive interviews with TikTok users and calculating the item-level face validity index. Our study population included 429 adults who have been TikTok users for at least the last 12 months. We employed exploratory and confirmatory factor analysis to examine the construct validity of the TikTok Addiction Scale (TTAS). We examined the concurrent validity by using the Bergen Social Media Addiction Scale (BSMAS), the Patient Health Questionnaire-4 (PHQ-4), and the Big Five Inventory-10 (BFI-10). We used Cronbach's alpha, McDonald's Omega, Cohen's kappa, and intraclass correlation coefficient to examine reliability.ResultsWe found that the TTAS is a six-factor 15-item scale with robust psychometric properties. Factor analysis revealed a six-factor structure, (1) salience, (2) mood modification, (3) tolerance, (4) withdrawal symptoms, (5) conflict, and (6) relapse, which accounted for 80.70% of the total variance. The concurrent validity of the TTAS was excellent since we found significant correlations between TTAS and BSMAS, PHQ-4, and BFI-10. Cronbach's alpha and McDonald's Omega for the TTAS were 0.911 and 0.914, respectively.ConclusionThe TTAS appears to be a short, easy-to-use, and valid scale to measure TikTok addiction. Considering the limitations of our study, we recommend the translation and validation of the TTAS in other languages and populations to further examine the validity of the scale.